2018
DOI: 10.3390/brainsci8070124
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts in Michigan HealthCare System; Racial Differences

Abstract: Background. Community-based studies have documented racial differences in social, psychiatric, and medical determinants of suicidal ideation; however, less is known about racial differences in the profile of suicide attempts in clinical settings. Aim. The current study aimed to compare Blacks and Whites who attempted suicide for demographic factors, socioeconomic status, medical history, psychiatric disorders, and outcomes. Methods. This retrospective study was a retrospective chart review of DataDirect, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…In other terms, race/ethnicity, gender, and SES have complex effects in depicting what poorer SRH means. 40,62,63 For example, education and income impact SRH of White but not AA individuals. [33][34][35] At the same time, SRH predicts mortality risk for Whites but not AAs.…”
Section: Discussionmentioning
confidence: 99%
“…In other terms, race/ethnicity, gender, and SES have complex effects in depicting what poorer SRH means. 40,62,63 For example, education and income impact SRH of White but not AA individuals. [33][34][35] At the same time, SRH predicts mortality risk for Whites but not AAs.…”
Section: Discussionmentioning
confidence: 99%
“…At least two studies have suggested racial differences exist in the effects of expanding health insurance on health [53,54]. Such reports reduce enthusiasm for expansion of health insurances as a core strategy to eliminate the health gap by race/ethnicity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of comorbidities between SES, physical health problems, health behaviors, and psychiatric disorders in AAs differ from those of Whites [35,36,37]. For example, obesity is a weaker risk factor for MDD for AAs than for Whites [38,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented race and race by gender variation in the correlations between MDD, anxiety, alcohol use, substance use, suicidality, and perceived health, perceived mental health need, and service use [35,37,43,50,51]. The Fragile Families and Child Well-Being compared AA ( n = 2407) and White ( n = 894) individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation